Meso- and axially-modified IrIIItriarylcorroles with tunable electrocatalytic properties. (April 2020) - Zhang, Xifeng; Wang, Yu; Zhu, Weihua; Mack, John; Soy, Rodah C.; Nyokong, Tebello; Liang, Xu
Abstract: The synthesis of three A2 B type Ir(III)triarylcorroles with meso -aryl substituents that provide electron donating (push) and withdrawing (pull) properties and three A3 type Ir III triphenylcorroles with differing pyridine axial ligands is reported, along with their structural characterization. An analysis of the structure-property relationships in the optical and redox properties has been carried out by comparing their optical spectroscopy and electrochemistry to trends predicted in DFT and TD-DFT calculations. The results demonstrate that A2 B type Ir III triarylcorroles are highly efficient electrocatalyzed oxygen reduction reactions (ORRs) and that their reactivity can be modulated by modulating the electronic structure by changing the nature of the meso -substituent at the B-positions, and even axial pyridine ligands. Highlights: Six A2 B push-pull type meso - and axial-modified Ir(III)triarylcorroles were reported. An analysis of optical spectroscopy and electrochemistry to trends predicted in DFT and TD-DFT calculations. These Ir III triarylcorroles are highly efficient and tunable electrocatalyzed oxygen reduction reactions (ORRs).